Psychological immunity among kindergarten teachers 1445 AH 2024 AD - Al Nuaimi, Noha Najm Abdullah khader (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2024)
The current research aims to identify the level of psychological immunity among kindergarten teachers in the city of Mosul and its right and left sides, and the research sample reached (95) kindergarten teachers in the city of Mosul, on the right side (45) teacher and the left side (50) teacher, and the researcher adopted the psychological immunity scale (Zidane, 2013), which was confirmed to be true and consistent, was applied to the research sample and obtain data and after processing them statistically using the arithmetic mean, standard deviation and Pearson correlation coefficient, And the T test for one sample, and the hypothetical mean, the results showed that there is a statistically significant difference in the level of psychological immunity of kindergarten teachers for the arithmetic average and the hypothetical average and in favor of the arithmetic average. Taking into consideration the findings of the study, the researcher delivered a collection of recommendations and proposals, which included the following: Benefiting from the psychological immunity scale prepared in the current research of the concerned educational authorities, especially the General Directorate of Education in Nineveh Governorate. Psychological immunity among primary school teachers and its relationship to their self-efficacy in light of some variables